2016
DOI: 10.1080/20440243.2016.1158455
|View full text |Cite
|
Sign up to set email alerts
|

A Concept Analysis of Spirituality in Occupational Therapy Practice

Abstract: analysis. Spirituality in occupational therapy practise is associated with a holistic, personcentred approach to care in order to restore a sense of wellbeing and recognise individual coping strategies. A framework for occupational therapy practice is offered to operationalise spiritual care for occupational therapists. The study concluded that occupational therapists respond to a disruption in well-being and quality of life by mobilising ritual coping strategies, to engender meaning and purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…Where, in particular, in the European contexts modernization, secularisation and persistence of strong religion beliefs co-exist are occurring in conjunction with increasing ethnic diversity associated with global migration. 5,8,10,11,17 –32…”
Section: Introductionmentioning
confidence: 99%
“…Where, in particular, in the European contexts modernization, secularisation and persistence of strong religion beliefs co-exist are occurring in conjunction with increasing ethnic diversity associated with global migration. 5,8,10,11,17 –32…”
Section: Introductionmentioning
confidence: 99%
“…Considering that spirituality is at the very core of occupational therapy practice, emphasised by its central placement within the CMOP-E model, there may be a discrepancy between occupational therapists' understanding and comfort when discussing spirituality. Barriers to exploring spirituality within practice include difficulty defining spirituality, therapists not wanting to impose their own beliefs, and not seeing it as a priority (Jones et al, 2016). Although occupation, spirituality, and the cultural environment were not thoroughly explored during occupational therapy interactions in this study, these factors may influence a person's experience with the mask and require further exploration in future studies to determine their relevance for people experiencing mask anxiety.…”
Section: Discussionmentioning
confidence: 95%
“…Many authors observe that spirituality strongly affects the recovery process (Holt et al, 2011; McColl, 2000; Owen et al, 2014). Jones et al (2016) in their work concluded that “occupational therapists respond to a disruption in wellbeing and quality of life by mobilising patients’ spiritual coping strategies in order to support and restore the patient’s sense of meaning and purpose” (p. 38).…”
Section: Discussionmentioning
confidence: 99%
“…Spirituality is considered important by occupational therapy practitioners (Engquist, Short-DeGraff, Gliner, & Oltjenbruns, 1997). Currently, the interest in spirituality is part of the contemporary paradigm of occupational therapy that is related to the return of therapy to its origins (Thompson & MacNeil, 2006), an attempt to find and describe various factors affecting occupational performance and engagement, as well as the opinion that the spiritual dimension of a person has an effect on his or her treatment, therapy, and rehabilitation (Jones, Topping, Wattis, & Smith, 2016;Taylor, Mitchell, Kenan, & Tacker, 2000). Teo (2009) indicates that the basic aim of occupational therapy is to provide the client with the choice of activities, as well as engagement in and control over these activities, which is connected with fulfilling human needs, the purpose of which is to promote health and well-being, as well as to increase the quality of life.…”
Section: Introductionmentioning
confidence: 99%